Ureteric stent versus percutaneous nephrostomy for acute ureteral obstruction - clinical outcome and quality of life: a bi-center prospective study - O. Shoshany; T. Erlich; S. Golan; N. Kleinmann; J. Baniel; B. Rosenzweig; A. Eisner; Y. Mor; J. Ramon; H. Winkler; D. Lifshitz (BMC Urology, 2019)
Abstract Background To compare quality of life (QoL) indices between ureteral stent (DJS) and nephrostomy tube (PCN) inserted in the setting of acute ureteral obstruction. Methods Prospective bi-centered study. Over the span of 2 years, 45 DJS and 30 PCN patients were recruited. Quality of life was assessed by 2 questionnaires, EuroQol EQ-5D and ‘Tube symptoms’ questionnaire, at 2 time points (at discharge after drainage and before definitive treatment). Results Patients’ demographics and pre-drainage data were similar. There were no clinically significant differences in patient’s recovery between the groups, including post procedural pain, defeverence, returning to baseline renal function, and septic shock complications. More DJS patients presented to the emergency room with complaints related to their procedure compared to PCN patients. At first, DJS patients complained more of urinary discomfort while PCN patients had worse symptoms relating to mobility and personal hygiene, with both groups achieving similar overall QoL score. At second time point, PCN patients’ symptoms ameliorated while symptoms in the DJS group remained similar, translating to higher overall QoL score in the PCN group. Conclusions The two techniques had a distinct and significantly different impact on quality of life. Over time, PCN patients’ symptoms relieve and their QoL improve, while DJS patients’ symptoms persist. Specific tube related symptoms, and their dynamics over time, should be a major determinant in choosing the appropriate drainage method, especially when definitive treatment is not imminent.